Avaliação das propriedades psicométricas da versão brasileira da BEHAVIORAL PAIN SCALE em vítimas de traumatismo cranioencefálico - Araújo, Raphael Almeida Santiago de (2017)
We aim to evaluate the psychometric properties of validity, reliability and responsiveness of the Brazilian version of the Behavioral Pain Scale (BPS-Br) in traumatic brain injury victims. This is an observational, cross-sectional, repeated-measure, and analytical study, performed in two ICUs within a Brazilian high-complexity public hospital. It was completed with 444 independent observations, a pairwise comparison and performed simultaneously before, during and after eye cleaning and endotracheal suctioning of thirty-seven adult patients with moderate to severe traumatic brain injury. The BPS-Br had good internal consistency (0.7 ≤ α ≤ 0.9), good discriminant validity (p < 0.001), moderate to excellent reliability based on inter-rater agreement (ICC = 0.66 – 1.00 e κ = 0.5 – 1.0), and high responsiveness (0.7 – 1.7). The upper limbs subscale had the highest score during the nociceptive procedure (1.8 ± 0.9). Deep sedation affected the increase of grading during painful procedures (p < 0.001). Our results suggest the BPS-Br is a useful tool for clinical practice to evaluate the pain experienced by this group of patients. Furthermore, it may also contribute to improvements in handling analgesia and sedation, which contributes to better outcomes for these patients. Perspective This article presents the psychometric properties of the Behavioral Pain Scale. This measure could potentially help clinicians assess pain in critically ill patients with traumatic brain injury and may contribute to improvement of pain management.